Invariant NKT cells promote skin wound healing by preventing a prolonged neutrophilic inflammatory response. Issue 5 (8th December 2017) - Tanno, Hiromasa; Kawakami, Kazuyoshi; Kanno, Emi; Suzuki, Aiko; Takagi, Naoyuki; Yamamoto, Hideki; Ishii, Keiko; Imai, Yoshimichi; Maruyama, Ryoko; Tachi, Masahiro
Abstract: The wound‐healing process consists of the inflammation, proliferation, and remodeling phases. In chronic wounds, the inflammation phase is prolonged with persistent neutrophil infiltration. The inflammatory response is critically regulated by cytokines and chemokines that are secreted from various immune cells. Recently, we showed that skin wound healing was delayed and the healing process was impaired under conditions lacking invariant natural killer T (iNKT) cells, an innate immune lymphocyte with potent immuno‐regulatory activity. In the present study, we investigated the effect of iNKT cell deficiency on the neutrophilic inflammatory response during the wound healing process. Neutrophil infiltration was prolonged in wound tissue in mice genetically lacking iNKT cells (Jα18KO mice) than in wild‐type (WT) control mice on days 1 and 3 after wounding. MIP‐2, KC, and IL‐17A were produced at a significantly higher level in Jα18KO mice than in WT mice. In addition, neutrophil apoptosis was significantly reduced in the wound tissue in Jα18KO mice than in WT mice. Treatment with anti‐IL‐17A mAb, anti‐Gr‐1 mAb, or neutrophil elastase inhibitor reversed the impaired wound healing in Jα18KO mice. These results suggest that iNKT cells may promote the wound healing process through preventing the prolonged inflammatory response mediated by neutrophils.